High little biological activity aeration control system for biological catalytic oxidation method - LUO TAO (2018)
The utility model discloses a high little biological activity aeration control system for biological catalytic oxidation method, including bio -contact oxidation tank, aeration equipment and controlling means, aeration equipment is the intercommunication bottom bio -contact oxidation tank, controlling means includes PLC the control unit, weisheng material consumption oxygen speed OUR apparatus, oxygen transfer efficiency OTE apparatus and DO dissolved oxygen meter are connected with the PLC the control unit electricity, and PLC the control unit is connected with the aeration equipment electricity, and weisheng material consumption oxygen speed OUR apparatus, oxygen transfer efficiency OTE apparatus and DO dissolved oxygen meter all set up in bio -contact oxidation tank. Consume oxygen speed OUR value, oxygen transfer efficiency OTE value and dissolved oxygen DO value, weisheng material consumption oxygen speed OUR value, oxygen transfer efficiency OTE value and dissolved oxygen DO value in the control aeratio